Enhanced production of compost from Andean wetland biomass using a bioreactor and photovoltaic system (2017)
Azolla filiculoides and Typha latifolia are invasive plants that detrimentally affect water and environmental quality in Andean wetlands. This study determined the aeration rate required to accelerate the composting process for biomass from these two plants using an enhanced semi-portable, closed, controlled bioreactor powered by a photovoltaic system. Such a system utilizing biomass from invasive aquatic plants could be used to produce compost in rural, remote, mountainous areas with little infrastructure. The solar powered, self-gyrating fixed bed gasifier bioreactor system measured tri-daily temperature, humidity, oxygen and pH. Aeration rate and humidity curves were also developed and could be used in other composting systems in tropical mountainous areas. The autonomous, self-powered, closed system bioreactor reduced composting time from the typical 9 weeks to just 4 and period of activation from 2.6 weeks to 1.5 days. Compost pH, humidity and C:N ratios were all within the range of reported values. Physical and chemical analyses show that the final compost material was suitable for local Andean cropping systems. The system can be used to sustainably utilize excess biomass residue material from Andean wetland restoration projects. © 2017 Elsevier Ltd